2016
DOI: 10.4028/www.scientific.net/msf.860.160
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of the Mechanics Performance about GFRP Tube Confined Concrete Short Column under the Axial Compression

Abstract: In order to study the axial compression performance of GFRP tube composite columns filled with concrete and better applied to engineering, the influence of different winding angle of GFRP tube, thickness of GFRP tube, concrete strength and the containing rate of steel are simulated by using finite element analysis software ABAQUS when the column under the axial compression ,The results show that: the numerical results are in good agreement with the experimental results; reduced GFRP tube winding angle, increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The research on the mechanical behavior of FRP-confined concrete under axial compression has dealt with normal-strength concrete (Song and Fan, 2016; Hadi et al, 2018; Zavvar et al, 2021). It was shown that the combination of FRP and concrete not only improved the ductility of concrete in the core area, improved the compression, bending and shear performance of composite columns, but also improved the utilization efficiency of FRP materials.…”
Section: Introductionmentioning
confidence: 99%
“…The research on the mechanical behavior of FRP-confined concrete under axial compression has dealt with normal-strength concrete (Song and Fan, 2016; Hadi et al, 2018; Zavvar et al, 2021). It was shown that the combination of FRP and concrete not only improved the ductility of concrete in the core area, improved the compression, bending and shear performance of composite columns, but also improved the utilization efficiency of FRP materials.…”
Section: Introductionmentioning
confidence: 99%